An autoethnographic exploration of the experiences of a 'black' female employee and doctoral student in higher education - Paulse, Juliet (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
This autoethnographic paper explores the lived experiences of a ‘black’ female employee and doctoral student within higher education spaces in post-apartheid South Africa. Anchored by personal narratives and reflexive analysis, it examines the intersections of individual aspirations, systemic inequities and cultural barriers shaped by colonial and apartheid legacies. This paper focuses on identity formation, resilience and agency within academic spaces, revealing the challenges and opportunities encountered in pursuing equity and inclusion. This paper draws on scholars such as Maria Lugones (2010) Sara Ahmed (2012; 2017) and Chandra Talpade Mohanty (1988; 2003), who provide critical insights into structural exclusion and the systemic constraints that hinder the advancement of marginalised identities. By relying on the theoretical lens of postcolonial feminism, this paper contributes not only to understanding the unique challenges faced by a ‘black’ female employee and doctoral student from a marginalised group but also advocates a reimagining of institutional structures to enhance diversity, inclusion and equity, as well as amplifying marginalised voices. The findings contribute to the literature on marginalised identities in higher education spaces and offer insights that might resonate with others in a similar position.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 9, 2025 Special Issue
Keywords: Autoethnography; ‘Black’ female employee; Doctoral journey; Post-apartheid South Africa; Identity; Inclusion; Post-apartheid era -- South Africa; Women employees; Doctoral students; Education, Higher -- South Africa